Erratum to: catalyst-free oxidation of sulfides to sulfoxides and diethylamine catalyzed oxidation of sulfides to sulfones using oxone as an oxidant - Kupwade, R. V. (Research on Chemical Intermediates, 2018)
We describe here our journey from the failure of our attempts in controlled oxidation of sulfides to sulfoxides using an Oxone®–KBr combination to our success in the development of a catalyst-free protocol for the oxidation of sulfides to sulfoxides using Oxone as an oxidant. We also describe the failure of our attempts at the oxidation of sulfides to sulfones using an excess of Oxone–KBr as well as Oxone, and our success towards the development of a rapid, scalable and chromatography-free protocol for the oxidation of sulfides to sulfones using diethylamine–Oxone as an unprecedented catalyst–oxidant combination.
Keywords: diethylamine; organocatalysis; Oxidation; Oxone; Sulfones; Sulfoxides

Tris-hydroxymethylaminomethane (THAM): An efficient organocatalyst in diversity-oriented and environmentally benign synthesis of spirochromenes - Khot, Supriya S.; Anbhule, Prashant V.; Desai, Uday V.; Wadgaonkar, Prakash P. (Comptes Rendus Chimie, 2018)
Tris-hydroxymethylaminomethane has been demonstrated to be an efficient organocatalyst in diversity-oriented synthesis of medicinally prevalent spirochromenes by one-pot, three-component reactions between isatins, malononitrile, and enolizable CH acids like dimedone, 4-hydroxycoumarin, 4-hydroxy-N-methylquinolin-2-one, or in situ generated 2-methylpyrazolon-2-one. Biodegradability and extremely low cost of the catalyst are the noteworthy features of this chromatography-free protocol.
Keywords: green chemistry; Multicomponent synthesis; organocatalysis; Spirochromenes; Tris-hydroxymethylaminomethane